Effect of photosynthetically elevated pH on performance of surface flow-constructed wetland planted with Phragmites australis - Yin, Xiaole; Jian Zhang; Hu, Zhen; Xie, Huijun; Guo, Wenshan; Qingsong Wang; Ngo, Huu Hao; Shuang Liang; Lu, Shaoyong; Wu, Weizhong (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2016)
Combination of emergent and submerged plants has been proved to be able to enhance pollutant removal efficiency of surface flow-constructed wetland (SFCW) during winter. However, intensive photosynthesis of submerged plants during summer would cause pH increase, which may have adverse effects on emergent plants. In this study, nitrogen transformation of lab-scale SFCW under pH gradient of 7.5, 8.5, 9.5 and 10.5 was systematically investigated. The results showed that total nitrogen (TN) removal efficiency decreased from 76.3 +/- 0.04 to 51.8 +/- 0.04 % when pH increased from 7.5 to 10.5, which was mainly attributed to plant assimilation decay and inhibition of microbe activities (i.e., nitrite-oxidizing bacteria and denitrifiers). Besides, the highest sediment adsorption in SFCW was observed at pH of 8.5. In general, the combination of submerged and emergent plants is feasible for most of the year, but precaution should be taken to mitigate the negative effect of high alkaline conditions when pH rises to above 8.5 in midsummer.